1988
DOI: 10.1177/153857448802200209
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Carotid Mycotic Pseudoaneurysm After Simple Carotid Endarterectomy: Case Report and Brief Literature Review

Abstract: Carotid pseudoaneurysm is an uncommon but serious complication of carotid endarterectomy. A case is presented in which the lesion occurred four weeks after combined aortocoronary bypass and carotid endarterectomy without patch angioplasty. The English surgical literature concerning this lesion is reviewed and reported. Case ReportA seventy-one-year-old diabetic white male presented to Riverside Methodist Hospitals on August 5, 1985, with claudication. A loud left carotid bruit was appreciated. Arteriography de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Nine of the 15 postsurgical reports highlight the importance of carotid endarterectomy as an underlying cause. 19,[24][25][26][27][28][29][30] Graver and Mulcare 27 performed a comprehensive review of postendarterectomy pseudoaneurysms, but only 6 of 50 cases involved infection. Dougherty et al 28 found that 1% to 3% of endarterectomy grafts were complicated by infection.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Nine of the 15 postsurgical reports highlight the importance of carotid endarterectomy as an underlying cause. 19,[24][25][26][27][28][29][30] Graver and Mulcare 27 performed a comprehensive review of postendarterectomy pseudoaneurysms, but only 6 of 50 cases involved infection. Dougherty et al 28 found that 1% to 3% of endarterectomy grafts were complicated by infection.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%